Spies and commandos how America lost the secret war in North Vietnam - Conboy, Kenneth J (Modern war studies, 2000)
"During the Vietnamese war, the United States sought to undermine Hanoi's subversion of the Saigon regime by sending Vietnamese operatives behind enemy line. A secret to most Americans, this covert operation was far from secret in Hanoi; all of the commandos were killed or captured, and many were turned by the Communitsts to report false information. [This book] traces the rise and demise of this secret operation started by the CIA in 1960 and expanded by the Pentagon beginning in 1964". -- Jacket